Klinefelter’s Syndrome and sexual offending: a literature review - O'Donovan, Rebecca; Völlm, Birgit (John Wiley & Sons, Ltd, 2017)
Background: Klinefelter’s Syndrome is a sex chromosome abnormality affecting approximately 1 in 1000 males. There have been suggestions that it is associated with a higher than average prevalence of sexual offending but to what extent does research evidence support this assertion? Aims: To conduct a systematic review of published research to establish the prevalence of sexual offending in males with Klinefelter’s Syndrome. Method: The databases MEDLINE, PsycINFO and EMBASE were searched from inception until 31st December 2016 using a range of terms for Klinefelter’s syndrome and for sexual offending. All selected papers were examined for quality using the STROBE (Strengthening of Observational Studies in Epidemiology) checklist. Results: We identified 53 relevant papers of which ten met our inclusion criteria. All but one were prevalence studies conducted in a prison or hospital setting. The one, Danish, register based cohort study did suggest an increased risk of sex offending among Klinefelter men, probably established before the diagnosis was made and, therefore, any hormone replacement instituted. Conclusion: There is insufficient evidence to date to support concerns about exceptional risk of sex offending among men with Klinefelter’s syndrome. Rather, it is arguable that there is a research gap in understanding how the experience of and treatment for their condition may affect them.